Analysing work-life balance and productivity of working mothers with children with special needs - Fanggidae, Rolland Epafras; Tadu, Ingrid Adinda; Nursiani , Ni Putu (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the effect of work-life balance (WLB) on the productivity of working mothers who have children with special needs in Kupang City, Indonesia. Methodology: Using an explanatory quantitative approach with PLS-SEM analysis. Data were collected from a random sample of working mothers in the area and analyzed using SmartPLS 4.0 software. Results: WLB significantly contributes to increased work productivity, with a path coefficient (?) of 0.728 and an R² value of 0.530, indicating that more than half of the productivity variation can be explained by WLB. The main supporting factors for WLB include family support, flexible organizational policies, and effective stress management. Conclusions: The study confirms that productivity success heavily depends on a holistically managed work-life balance through adaptive policies and social support. The additional pressure from the responsibility of having children with special needs requires a support system to prevent productivity decline, highlighting the importance of managing role conflicts and emotional exhaustion. Limitations: This study is limited by its cross-sectional design, localized sample in Kupang City, and reliance on self-reported data. It does not explore qualitative aspects or moderating factors such as job type, support systems, or the severity of the child’s condition, which may influence the results. Contribution: Enriches the human resource management and industrial psychology literature with empirical contextual insights from Indonesia and offers practical recommendations for organizations and policymakers to support working mothers with children who have special needs.